Impact of antenatal depressive and anxiety symptoms on adverse birth outcomes in Baghdad, Iraq: a prospective cohort study - Ola Ali Nassr; Mohammed Mahmood Mohammed; Hind abdulkhaliq Showman (College of Pharmacy / Mustansiriyah University, 2023)
Background: Psychiatric symptoms are common during pregnancy, potentially leading to an increased risk of adverse birth outcomes. Studies assessing the impact of depression and/or anxiety on adverse birth outcomes in Iraq are currently lacking. This study aims to   determine whether depression and/or anxiety is independently associated with preterm birth (PTB) and low birth weight (LBW). Methods: A prospective cohort study included 352 pregnant women from outpatient clinics of Al-Yarmouk hospital and private clinics in Baghdad, Iraq from March 2021 to February 2022 using a convenience sampling. They were screened for depression using Edinburgh Postnatal Depression Scale (EPDS) during pregnancy and followed up to assess adverse birth outcomes. Multivariable logistic regression was used to determine predictors associated with adverse birth outcomes. Results: The prevalence of PTB and LBW was 7.7% and 11.6%, respectively. After adjustment of all potential sociodemographic, clinical and obstetric confounders, depression was independently associated with giving birth to LBW neonate (odd ratio (OR):3.64; 95% confidence interval (CI) 1.70, 7.79), but not PTB. Prevalence of LBW in depressed was 21.2% compared to 7.7% for non-depressed. LBW was also associated with a history of LBW and PTB. In contrast, anxiety did not seem to affect birth outcomes. Conclusion: Depression during pregnancy, regardless of the trimester, is independently associated with a higher likelihood of giving birth to LBW neonates (OR: 3.64; 95% CI 1.70, 7.79). Effective interventions that target maternal depression are vital to decrease morbidity and mortality associated with LBW.